The role of digital pawn and bullion markets in strengthening financial inclusion - Handi Wilujeng Nugroho; Zakiyah Ulfa Aryani (Institute for Advanced Social, Science, and Sustainable Future, 2026)
Background: Financial inclusion in Indonesia continues to face structural barriers, particularly among informal households and micro-enterprises that remain underserved by conventional banking systems. Although financial technology has expanded access to digital finance, unsecured digital lending has also generated concerns regarding over-indebtedness and systemic vulnerability. Digital gold pawn and bullion services offer an alternative inclusion model based on real-asset collateral. Methods: This study employs an integrated mixed-method approach combining descriptive quantitative analysis of secondary data from 2018–2024 with qualitative examination of financial regulations and governance frameworks related to digital gold-based finance. Findings: The findings indicate significant growth in digital gold pawn users, transaction values, and bullion accounts, particularly among unbanked populations and micro-enterprises. Gold-backed financing demonstrates lower default risk and more stable performance than unsecured digital credit due to the stabilizing role of tangible collateral. Digital integration has expanded geographic outreach and improved transaction efficiency, although regulatory fragmentation and uneven consumer protection remain important challenges. Conclusion: Digital gold-based finance can strengthen financial inclusion without undermining systemic resilience when technological scalability is structurally aligned with real-asset discipline and harmonized oversight. Novelty/Originality of this article: The study advances a hybrid financial inclusion framework that connects informal asset ownership with formal financial systems, and empirically demonstrates how asset-backed digital intermediation reshapes risk allocation, access dynamics, and stability outcomes within a developing digital economy.